The role of soluble toll-like receptor-2 and 4 in children with pneumonia: a combined analysis of saliva and serum samples - Necipoglu, Ozlem; Demir, Osman Oguz; Aykac, Kubra; Karahan, Sevilay; Cengiz, Ali Bulent; Aydin, Malik; Ozsurekci, Yasemin (Frontiers in Immunology, 2026)
BackgroundSince rapid and accurate diagnosis of pneumonia and determination of its severity remain challenging, particularly in childhood, we aimed to evaluate the role of toll-like receptors (TLR) in pneumonia, which has been limited in animal and adult studies.MethodsIn this study, TLR-2, TLR-4, interleukin (IL)-1β, IL-4, IL-6, IL-10, interferon (IFN)-α, and tumor necrosis factor (TNF)-α levels were measured in serum samples of n = 67 pediatric patients with community acquired pneumonia (CAP) (43 inpatients and 24 outpatients) and 22 healthy pediatric controls. Saliva samples of n = 30 pediatric patients with CAP (19 inpatients and 11 outpatients) and 19 healthy pediatric controls were also investigated to analyze the expression of these cytokines and TLRs.ResultsIn saliva samples taken at the time of diagnosis, threshold levels of TLR-2 were 1.16 2-ΔΔCt and of TLR-4 1.28 2-ΔΔCt differentiating patients with and without pneumonia. The sensitivity of salivary TLR-2 and TLR-4 tests were found to be 0.80 and 0.86, respectively. In serum samples, soluble TLR-2 and TLR-4, IL-1β, IL-4, IL-6, Il-10, IFN-α, and TNF-α levels were significantly decreased in patients with coronavirus disease-19 (COVID-19) as compared with other viruses (p < 0.05 in each). Only one mortal case was present in the inpatient group during the study period.ConclusionThis study demonstrates that salivary TNF-α, soluble TLR-2 and TLR-4 may serve as promising non-invasive biomarkers for diagnosing and stratifying pediatric pneumonia.